The relationship between network capabilities and innovation performance: Evidence from Chinese high-tech industry. Issue 8 (9th September 2019) - Fang, Gang; Zhou, Qing; Wu, Jian; Qi, Xiaoguang
Abstract : Purpose: Innovation networks provide an efficient mechanism for organizations to realize their potential for knowledge learning and innovation improvement. Firms situated within innovation networks require specific abilities to acquire the knowledge and the complementary assets that facilitate their innovation performance. Motivated by recent research studies in the area of social network and RBV, the purpose of this paper is to improve the understanding of the precise manner in which network capability affects a firm's innovation performance. Design/methodology/approach: Based on the data obtained from Chinese high-tech firms, the hypotheses are tested by using hierarchical multiple regressions. Findings: This study identifies two types of network capabilities: network structural capability and network relational capability. The findings suggest that network structural capability has a greater positive impact on innovation performance than network relational capability does within an exploration-orientated network. However, network relational capability is more positively associated with innovation performance within an exploitation-orientated network. Practical implications: A firm can enhance the value of its ego network by shaping and adjusting network configurations, rather than by passively reaping the benefits from existing relationships or ties with partners. Originality/value: This paper contributes to strategic management theory and social network theory by illustrating how a networked firm can enable network value and appropriate this value according to its strategic purposes and by suggesting that a firm can improve its ego network's value through exerting its network capabilities to shape and adjust network configurations. This paper also advances the contingent approach within social network research by offering a new complementary perspective and new evidence from a Chinese context.